The characterisation of sexual behaviour in Chinese male university students who have sex with other men: A cross-sectional study - Zhang Dandan; Pan Xiaohong; Ma Qiaoqin; Xu Guozhang; Ono-Kihara Masako; Cong Liming; Homma Takayuki; Kihara Masahiro (BMC, 2008)
Abstract Background The risks for Chinese male university students who have sex with other men (MSM) have not been compared with those for non-MSM students. This information is important for the development of targeted HIV prevention programmes for this population. Methods Sexually active MSM and non-MSM students were compared for demographic characteristics, sexual behaviour, and related psychosocial variables using bivariate analyses. The data were a subset drawn from a large-scale cross-sectional questionnaire survey of sexually active male students conducted at two universities in a large city in Zhejiang Province, China, in 2003. Results Of 1824 sexually active male students, 68 (3.7%) reported having had sex with a man at least once; 33.8% of these 68 men had also had female partners. Compared with non-MSM students, MSM students were 3-6.5 times more likely to have had sexual encounters with casual or commercial sex partners and were three times less likely to have protected sex in the past year or during their lifetime. They were three to five times more likely to have had multiple partners and 15 times more likely to have had a sexually transmitted disease (STD). In addition, the MSM students knew half as much about HIV and had less condom-decision than did non-MSM students and were two times more accepting of commercial sex. However, the MSM students were twice as aware of the risks for HIV infection. Conclusion MSM composed 3-4% of the male sexually active university student population studied and was found to be at greater risk than non-MSM students for STD/HIV infection. There is an urgent need for STD/HIV programmes in university health services that take into consideration the sexuality and psychosocial issues of MSM students.